Proposta de um modelo de processos de negócios para inovação aberta em indústrias com foco em startups - Buzatto, Henrique Kozlowiski (2020)
The open innovation in a competitive scenario is seen by organizations as an opportunity to achieve and keep competitive advantages. However, with the increase of the interest about open innovation in organizations, emerges the question about how to do open innovation in an effective way, point it is special sensitive for the industries. In that context, shows up as a research opportunity, the definition of an open innovation process model for industries, which is the goal of that research. For this, the methodology used was the Design Research Methodology (DRM), which consists of a preliminary study to understand the context and to set goals, and in the application and evaluation of the proposed solutions. In that context, it was been collected data, about open innovation models and how ope innovation is done in industries. As methodological research procedures, it was realized a bibliographic research and a field research in an industry, which the goal of map the open innovation process in this industry. For the model's construction, it was choosing to create a business process model based on the Business Process Modeling Notation (BPMN). For the model's elaboration, it was used as main technique the business process reengineering, which was used together with the business process management's concepts, and with the Value Stream Mapping (VSM) technique. In the present study, its presented the proposed model, the changes that occurred in the transition from the initial model identified to the proposed model, how the model itself works. Finally, it is made an analysis of the application of the proposed model in a real scenario, a comparison of the proposed model with the reference models used, and are presented the data obtained with the application of the proposed model in a real scenario in an industry.